(untitled) (Research, Society and Development, 2021)
Brazil is among the main beef producers, being the main exporter of this food and holder the second largest herd in the world. The production of Brazilian beef has often been associated as a generator of great environmental impact, but the particularities of the Brazilian production system based on pastures is usually not taken into account. Due these facts, the objective of this bibliographical review was gather information and discuss the environmental liabilities, associated with Brazilians beef cattle production systems. It was possible identify that are a large variation in emissions between production systems according to geographic location. The cattle production in well-managed pastures, as well the use of some technologies such supplementation, either with bulky or concentrated feed, in order to reduce the empty forage, can be significantly reduce the environmental liability of this activity. The emission of greenhouse gases by Brazilian beef cattle farming is similar or even lower than other countries.